Integration of Rap1 and Calcium Signaling - Ramoji Kosuru (International Journal of Molecular Sciences, 2020)
Ca2+ is a universal intracellular signal. The modulation of cytoplasmic Ca2+ concentration regulates a plethora of cellular processes, such as: synaptic plasticity, neuronal survival, chemotaxis of immune cells, platelet aggregation, vasodilation, and cardiac excitation−contraction coupling. Rap1 GTPases are ubiquitously expressed binary switches that alternate between active and inactive states and are regulated by diverse families of guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). Active Rap1 couples extracellular stimulation with intracellular signaling through secondary messengers—cyclic adenosine monophosphate (cAMP), Ca2+, and diacylglycerol (DAG). Much evidence indicates that Rap1 signaling intersects with Ca2+ signaling pathways to control the important cellular functions of platelet activation or neuronal plasticity. Rap1 acts as an effector of Ca2+ signaling when activated by mechanisms involving Ca2+ and DAG-activated (CalDAG-) GEFs. Conversely, activated by other GEFs, such as cAMP-dependent GEF Epac, Rap1 controls cytoplasmic Ca2+ levels. It does so by regulating the activity of Ca2+ signaling proteins such as sarcoendoplasmic reticulum Ca2+-ATPase (SERCA). In this review, we focus on the physiological significance of the links between Rap1 and Ca2+ signaling and emphasize the molecular interactions that may offer new targets for the therapy of Alzheimer’s disease, hypertension, and atherosclerosis, among other diseases.